Location of a new ice core site at Talos Dome (East Antarctica) - Stefano Urbini; Ignazio E. Tabacco; Massimo Frezzotti; Achille Zirizzotti; Cesidio Bianchi; Lili Cafarella (Annals of Geophysics, 2009)
In the frame of glaciology and palaeoclimate research, Talos Dome (72°48lS; 159°06lE), an ice dome on the East Antarctic plateau, represents the new selected site for a new deep ice core drilling. The increasing interest in this re- gion is due to the fact that the ice accumulation is higher here than in other domes in East Antarctica. A new deep drilling in this site could give important information about the climate changes near the coast. Previous papers showed that the dome summit is situated above a sloped bedrock. A new position on a relatively flat bedrock 5-6 km far from here in the SE direction was defined as a possible new ice core site for an European (Italy, France, Swiss and United Kingdom) drilling project named as TALDICE (TALos Dome Ice Core Project). This point, named as ID1 (159°11l00mE; 72°49l40mS), became the centre of the Radio Echo Sounding (RES) flight plan during the 2003 Italian Antarctic expedition, with the aim of confirming the new drilling site choice. In this paper 2001 and 2003 RES data sets have been used to draw a better resolution of ice thickness, bottom morphology and internal layering of a restricted area around the dome. Based on the final results, point ID1 has been confirmed as the new coring site. Fi- nally, the preliminary operations about the installation of the summer ice core camp (TALDICE) at ID1 site carried out during the XX Italian Antarctic expedition (November 2004-December 2005) are briefly described.